Public Perceptions of the Seriousness of Crimes: To What Extent are They Driven by Television Exposure? - Adriaenssen, An (European journal on criminal policy and research, 2020)
This article investigates the relationship between exposure to overall television content and television news on the one hand, and public crime seriousness perceptions, including the two main components of perceived crime seriousness, i.e., perceived wrongfulness and harm severity, on the other hand. Drawing on cultivation theory and additional literature, we have constructed three hypothetical models which, for the first time, also include conservationism and legal cynicism as mediating variables. Using structural equation modelling, we have tested the models empirically in a cross-sectional survey of 1278 adult Dutch-speaking Belgian residents. Our findings indicate that overall exposure to television content is not significantly related to perceived crime seriousness, wrongfulness, harm severity, or any of the mediating variables. Exposure to television news, however, is both directly and indirectly related to perceived crime seriousness, wrongfulness, and harm severity. These findings thus suggest the relevance of television news exposure as a predictor of people’s perceptions of crime seriousness.